Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

L’accès en anglais aux services de santé et aux services sociaux au Québec. Version française du rapport comparatif 2023-2019 - CROP (Community Health & Social Services Network, 2024)

Situation des populations de langue anglaise au Québec et de langue française au Canada hors Québec : résultats de l’Enquête sur la population de langue officielle en situation minoritaire de 2022 - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
Ce rapport présente les principaux résultats de l’Enquête sur la population de langue officielle en situation minoritaire (EPLOSM) de 2022. Il brosse un portrait d’ensemble de la situation des populations de langue anglaise au Québec et de langue française dans les autres provinces et les capitales des territoires du Canada. Cette enquête a été menée afin de mieux comprendre la situation des personnes de langue officielle en situation minoritaire en ce qui concerne certains sujets et enjeux actuels, comme la scolarité, les services à la petite enfance, l’accès à d’autres services dans la langue officielle minoritaire et leur utilisation, ainsi que les pratiques linguistiques à la maison, au travail et dans l’espace public. L’enquête, qui représente une collaboration entre Statistique Canada et Patrimoine canadien, vise à soutenir les utilisateurs de données sur les communautés de langue officielle en situation minoritaire. L’Enquête sur la population de langue officielle en situation minoritaire de 2022 est une enquête postcensitaire, c’est‐à‐dire que son échantillon provient du Recensement de la population de 2021. La population de langue officielle en situation minoritaire désigne la population de langue anglaise au Québec et la population de langue française au Canada hors du Québec. L’enquête a été menée dans les 10 provinces canadiennes du 16 mai au 16 décembre 2022, ainsi que dans les capitales des trois territoires canadiens du 22 août au 16 décembre 2022. Au total, près de 30 000 personnes y ont répondu. L’échantillon des adultes comprend 13 892 répondants, alors que l’échantillon des enfants compte 16 066 enfants pour lesquels un parent ou un tuteur a répondu à certaines questions portant sur leur enfant et à d’autres portant sur eux‐mêmes.

Situation of English-speaking populations in Quebec and French-speaking populations in Canada outside Quebec: Results of the 2022 Survey on the Official Language Minority Population - Pépin‑Filion, Dominique; Cornelissen, Louis; Lemyre, Étienne (Statistique Canada, 2024)
The 2022 Survey on the Official Language Minority Population (SOLMP) was conducted to shed light on different aspects of the situation of the English‐speaking population in Quebec and the French‐speaking populations in Canada’s other provinces and the territory capitals. This report presents the key findings from the 2022 Survey on the Official Language Minority Population (SOLMP). It provides an overview of the situation of English‐speaking populations in Quebec and French‐speaking populations in Canada’s other provinces and the territory capitals. This survey was conducted to better understand the situation of official language minorities with respect to certain topics and current issues, such as education, early childhood services, access to and use of other services in the minority official language, as well as language practices at home, at work and in the public sphere. The survey, which represents a collaboration between Statistics Canada and Canadian Heritage, aims to support users of data on official language minority communities.

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)